Combined test procedures in the meta-analysis of controlled clinical trials - Guido Knapp; Joachim Hartung (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
Concerning the actual significance level, we investigate the commonly used combined test procedures of meta-analysis, which contain the choice of the model, in which the analysis is carried out, and the commonly used tests for treatment effect in the fixed and random effects model, and some new combined test procedures, which use an alternative test statistic in the random effects model or the t-distribution as test distribution of the commonly used test statistics. A simulation study indicates that the new combined test procedures are better with respect to a prescribed significance level.
Keywords: 519